THE INFLUENCE OF COMMUNICATION IN CREATING HOUSEHOLD HARMONY IN ACEH BARAT DISTRICT - AR, Baharuddin; Nurainiah, Nurainiah (JURNAL AL-IJTIMAIYYAH, 2024)
Family harmony is a state where family members are united, each member fulfills their rights and obligations, affection is fostered, and mutual understanding, dialogue, and cooperation are well established, resulting in physical and spiritual well-being. This study aims to understand communication patterns in creating a harmonious household, analyze communication aspects influencing household harmony, and identify obstacles in creating a harmonious household. This research uses qualitative methods, where the researcher comprehensively examines the facts in the field according to the focus of the problem. The data obtained is then analyzed, presented, and discussed. Accurate and reliable data were collected through observation, interviews, and documentation techniques. The results of the study indicate that (1) communication patterns that can create household harmony include interpersonal communication, mutual trust and understanding, direct communication, and gentle communication; (2) communication aspects affecting household harmony include communication patterns and adjustments, the busyness of both spouses, financial issues, poor parenting, and lack of mutual trust. On the other hand, poor and ineffective communication results in household disharmony, as communication within the household is the main element for expressing all household life issues, and everything must be communicated openly and transparently. (3) obstacles to creating a harmonious household include poor communication, family aspects, economic aspects, infidelity, and lack of cooperation in nurturing, caring for, and guiding children. The responsibility for children is entirely handed over to the wife. At the same time, the husband only focuses on earning a living, thinking he must provide financially without assisting with household affairs. However, in maintaining a household, cooperation in all matters is essential.